ERSPLORASI MA PROGRAM RETERAMPILAN MENJADI MA KEJURUAN - Rohmat Mulyana (Badan Litbang dan Diklat Kementerian Agama RI, 2005)
This article discloses the two sides of needs in eliciting information, i.e. first evaluating the continuance of skill programs at Madrasah Aliyah, and second, predicting the feasibility degree and the readiness of madrasahs and their administrators in facing the possibility of the change of status to a vocational school (MAK). This article also sheds light on the real condition of the administration of skill programs at Madrasah Aliyah in the last two _years and the feasibility degree as well as the extent of their readiness when the present MAN is converted to vocational school.